Disseminated bony metastases following incidental gallbladder cancer detected after laparoscopic cholecystectomy - Youssef, F (2003)
BACKGROUND: In patients with gallbladder cancer bony metastases are usually a late feature. CASE OUTLINE: A 47-year-old woman presented with a 2-month history of right upper quadrant pain. Ultrasound scan showed gallstones and a thick-walled gallbladder. Laparoscopic cholecystectomy was performed. Histopathology showed poorly differentiated adenocarcinoma infiltrating the muscular layer and vascular invasion. She was referred for further surgery. Staging CT scan of the abdomen showed no local residual disease. However Tc-99 bone scan suggested disseminated bony metastases, which were confirmed by bone trephine biopsy. The cancer progressed rapidly and the patient died 4 months after the diagnosis. DISCUSSION: Bone metastases can occur with early gallbladder cancer and a radioisotope bone scan can avoid unnecessary extensive liver surgery.